Quercetin Liposomal Nanoformulation for Ischemia and Reperfusion Injury Treatment - Ferreira‐silva, Margarida (2022)
PD/BD/135264/2017 UID/DTP/04138/2020 UIDP/04138/2020 UIDP/04378/2020 UIDB/04378/2020 LA/P/0140/2020 UIDB/50006/2020 UIDB/00100/2020